The Influence of Leadership and Organizational Culture on Job Promotion Through Work Commitment at The Regional Office of The National Land Agency in Gorontalo Province - Hamim, Suci Handayani; Sulila, Ismet; Abdussamad, Juriko (Abdurrauf Science and Society, 2025)
This study aims to analyze the influence of leadership and organizational culture on the job promotion of civil servants at the Regional Office of the National Land Agency in Gorontalo Province, with work commitment as a mediating variable. A quantitative research method with a descriptive design was employed, using Structural Equation Modeling-Partial Least Squares (SEM-PLS) for data analysis. Data were collected through questionnaires distributed to 71 selected employees using purposive sampling. The results show that leadership has a positive and significant effect on work commitment, and organizational culture also exerts a positive and significant influence. Although leadership does not have a direct significant effect on job promotion, work commitment is found to significantly mediate the relationship between leadership and job promotion. Organizational culture has a positive impact on job promotion both directly and indirectly through work commitment. The study concludes that job promotion should be based on an objective and transparent merit system, supported by the development of positive leadership and organizational culture. These findings are expected to contribute to the advancement of human resource management in the public sector, particularly in enhancing the effectiveness of job promotion processes.